Protocol for mapping of the supplementary motor area using repetitive navigated transcranial magnetic stimulation - Engelhardt, Melina; Kern, Giulia; Karhu, Jari; Picht, Thomas (Frontiers in Neuroscience, 2023)
Background: Damage to the supplementary motor area (SMA) can lead to impairments of motor and language function. A detailed preoperative mapping of functional boarders of the SMA could therefore aid preoperative diagnostics in these patients. Objective: The aim of this study was the development of a repetitive nTMS protocol for non-invasive functional mapping of the SMA while assuring effects are caused by SMA rather than M1 activation. Methods: The SMA in the dominant hemisphere of twelve healthy subjects (28.2±7.7 years, 6 females) was mapped using repetitive nTMS at 20 Hz (120% RMT), while subjects performed a finger tapping task. Reductions in finger taps were classified in three error categories (≤15% = no errors, 15%-30% = mild, >30% significant). The location and category of induced errors was marked in each subject’s individual MRI. Effects of SMA stimulation were then directly compared to effects of M1 stimulation in four different tasks (finger tapping, writing, line tracing, targeting circles). Results: Mapping of the SMA was possible for all subjects, yet effect sizes varied. Stimulation of the SMA led to a significant reduction of finger taps compared to baseline (BL: 45taps, SMA: 35.5taps; p<0.01). Line tracing, writing and targeting of circles was less accurate during SMA compared to M1 stimulation. Conclusion: Mapping of the SMA using repetitive nTMS is feasible. While errors induced in the SMA are not entirely independent of M1, disruption of the SMA induces functionally distinct errors. These error maps can aid preoperative diagnostics in patients with SMA related lesions.